Hyperinsulinemia, cancer and maqui berry: The promise of nutritional supplementation - Brett Deters; Mir Saleem (Food Science and Human Wellness)
Nutritional supplementation has long been studied as a possible treatment alternative or as an adjunct to the standard treatments for common ailments and diseases. According to the latest research, the Chilean maqui berry, Aristotelia chilensis, has been shown to reduce postprandial insulin levels by as much as fifty percent. The berry, which has been shown to be as effective as metformin at increasing insulin sensitivity and controlling blood glucose levels, follows a simple mechanism of action that involves the inhibition of sodium dependent glucose transporters in the small intestine, slowing the rate at which sugars enter the bloodstream and thereby decreasing blood sugar spikes and the corresponding increase in insulin levels. Chronically high blood glucose levels have been proven to play a significant role in the development of cancers, as diabetics and prediabetics have been proven to have elevated risk of developing cancerous growth. Consistent dietary supplementation with maqui berry may therefore indirectly reduce the risk of cancer, as well as other diseases which respond negatively to hyperglycemia and hyperinsulinemia. Keywords: Hyperinsulinemia, Cardiovascular disease, Diabetes, Insulin, Maqui berry, Cancer